Empreendedorismo regional, redes e capital social: estudo de caso em dois APLs de confecção do Estado do Paraná - Calderari, Egon Bianchini (2019)
Regional entrepreneurship with a focus on the social dimension, in particular, the importance of social networks and capital to promote their empowerment has been the subject of recent research in academia (JULIEN, 2010; JOHANSSON, 2009). On the other hand, the role of the state to promote and/or strengthen regional entrepreneurship through actions that encourage local productive arrangements do not always achieve the expected results, partly due to the local social dimension. To understand such theoretical and empirical complexity, this descriptive-exploratory work aimed to identify how social capital manifests itself in the social networks of entrepreneurs present in the Maringá-Cianorte and Southwestern Local Productive Arrangements (APLs) from Paraná. To achieve the proposed objective, qualitative research was developed that adopted the incorporated case study as a method, treating each of the APLs as a distinct unit of analysis. APLs were first characterized historically and quantitatively (through descriptive statistical analyzes), from secondary data collected through documentary research on sites of the entities participating in APLs and accessed through public data platforms. Subsequently, semi-structured interviews were carried out with 14 inductors of APLs, identified from characterization studies and research carried out with these structures as objects. As a complement to the fieldwork, the direct observation technique was used to collect field notes. The field-collected primary data were integrally transcribed and then analyzed from the content analysis technique. The data were triangulated with the empirical theoretical framework established for the project, seeking the possibility of analytical generalization. The main contribution of the present study was an institutional analysis of the manifestations of social capital, which allowed the understanding of how the interactions between the networks and the context occur in APL and how social capital is manifested by the groups of actors, being used as a means to obtain resources present in the regional socioeconomic structure by the entrepreneurs. Cooperation between business groups and other organizations, however, has declined over the last few years and inter-regional rivalry has been heightened, as a result of the worsening of the country's economic situation and the absence of a political agenda directed to the sector, which occurs most markedly in the Maringá-Cianorte APL. The governance structure present in the Southwest APL, centered on one of the entities of corporate representativeness, still maintains itself as a strong inductive actor, capable of coordinating several actions for the benefit of the sector. It is considered that there is, however, no confidence and cooperative practices disseminated between the groups present in both APL, being restricted intragroup relations. It should be noted that social capital is predominantly manifested in smaller groups, characterized by the existence of informal networks developed between the entrepreneurs and their families or between groups already constituted in the APL, characterized by the bonds of friendship.